Listening to Sad Music: a Narrative Review - Ny, Cheah Pei; Wing, Cheong Ku (Universitas Negeri Semarang, 2024)
As noted in the tragedy paradox, the enjoyment of negative emotions evoked in artworks is a phenomenon acknowledged from ancient times to the present. Sad music listening induces a diverse range of emotional responses in the listener: some would experience pleasure, while others find it unpleasant; hence, this review aims to categorise sad music listening from the philosophical, psychological, sociological, and scientific perspectives. This review includes studies of journal articles, review articles, books, and book chapters from 2010-2022. The philosophical perspective reviewed the paradox of the attraction towards sad music. The psychological perspective reviewed the empirical studies that examined various factors contributing to enjoying sad music. The sociological perspective reviewed how sad music can be used to create a social connection. The scientific perspective reviewed the biological effects of sad music listening. Many of the studies found are related to the psychological perspective, in which sad music can induce diverse emotions, and there are several factors that contribute to the enjoyment of sad music. As more scientific research has been emerging in recent years, future research can explore the brain correlates and hormonal stimulation in various individual differences to consolidate why some people enjoy sad music while others do not.